Estudio de factibilidad para la implementación de una aplicación web para el control y seguimiento de ventas en la empresa Alfa LAN Center de la ciudad de Montalvo - Espín Fernández, Segundo José (2021)
The present case study called as a feasibility study for the implementation of a web application for the control and monitoring of sales in the company "Alfa LAN Center" in the city of Montalvo. Presents the lack of a computer system to control and monitor sales. Its objective was to evaluate the feasibility study of the implementation of a web application for the control and monitoring of sales in the company "Alfa LAN Center" in the city of Montalvo. In the investigation, the following methods were used: indicative and deductive, in addition to a descriptive investigation. The techniques that were used were direct observation and the survey by means of the questionnaire instrument made to the owner of the company, the findings presented the lack of control and monitoring of sales, they do not have a backing of the information that was presented In the collection of information Therefore, in conclusion it could be determined that this project is feasible, it was evaluated through the technical, operational and economic feasibility, therefore it complies with the necessary resources such as computer equipment, personnel and the necessary infrastructure to the implementation of the web application in the company "Alfa LAN Center".